THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY (BY THE LECTURER OF ISLAMIC STATE UNIVERSITY OF RADEN FATAH PALEMBANG - Nyayu Khodijah; Herman Zaini; Enok Rohayati (Ta'dib: Jurnal Pendidikan Islam, 2015)
This study aimed to examine the use of ICT by lecturers of Raden Fatah Islamic State Univercity and the factors that influenced it. The research used a quantitative approach with survey method. The research was conducted in May-July 2014. The data was collected using a questionnaire. Respondents were lecturers of UIN Raden Fatah totaling 86 people. Analysisof data usingunivariate, bivariate, andmultivariate techniques. The results showed that: 1) the use of ICT by lecturers of Raden Fatah Islamic State University was still not maximum, 2) the age, sex, level of education, teaching experience, andmotivation of the lecturers does not significantly affect theuse of ICTby lecturers, 3) the rewards factor had given significantly affect the use of ICT by lecturers, and 4) therewards factor hadthe most influence onthe use ofICTby lecturers ofRaden Fatah Islamic State University.